2011
DOI: 10.1155/2011/645643
|View full text |Cite
|
Sign up to set email alerts
|

Lower Frequency of CD62Lhighand Higher Frequency of TNFR2+Tregs Are Associated with Inflammatory Conditions in Type 1 Diabetic Patients

Abstract: Diabetes type 1 is a chronic autoimmune disease in which insulin-producing cells are gradually destroyed by autoreactive T cells. Human regulatory cells play important role in controlling autoimmunity, and their qualitative or quantitative dysfunctions may result in ineffective suppression of autoreactive T cells. CD62L is a surface molecule that plays role in homing capabilities of Tregs, and only cells with high expression of CD62L have high suppressive potential. Tregs are also characterized by the constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…In our cohort, we observed that children with either T1D or coeliac disease had a lower MFI of T reg cells (CD4 + CD25 hi ) compared to healthy controls or children diagnosed with both these diseases in combination. A decreased frequency of T regs (CD4 + CD25 + ) in T1D patients has also been observed previously . Currently, there is no precise definition of T reg cells in humans.…”
Section: Discussionsupporting
confidence: 75%
“…In our cohort, we observed that children with either T1D or coeliac disease had a lower MFI of T reg cells (CD4 + CD25 hi ) compared to healthy controls or children diagnosed with both these diseases in combination. A decreased frequency of T regs (CD4 + CD25 + ) in T1D patients has also been observed previously . Currently, there is no precise definition of T reg cells in humans.…”
Section: Discussionsupporting
confidence: 75%
“…Our previous studies have shown the impaired quantitative as well as qualitative properties of Foxp3 + Tregs in type 1 diabetic children [26, 27]. These impairments were probably dependant on an ongoing inflammatory response in these children.…”
Section: Introductionmentioning
confidence: 91%
“…The role of distinct Treg subsets in AML is currently not known, however, a functionally active Treg subset should have a high bone marrow migratory capacity (16). TNF receptor-2 (TNFR2) expression has recently been demonstrated to identify highly functional Tregs in healthy donors (17,18) and in various diseases such as malaria (19), diabetes (20), and cancer (21). TNFR2…”
Section: Introductionmentioning
confidence: 99%